The Use of Coconut Fiber as an Enhancer to the Bentonite Water-Based Drilling Fluid - Zairil Aznin, Mohammad Zahin Azhari; Misdan, Nurasyikin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Drilling fluids are a type of fluid that is continuously circulated during drilling operations. Awareness about the environment and health were not given much attention in order to focus on using harmful chemicals in drilling fluids to make it flow better. The bentonite water-based drilling fluid was enhanced using coconut fiber ash. The coconut fiber ash was mixed with bentonite and tap water in a beaker. The analysis of the drilling fluid was done using pH paper and Viscolite 700HP Bench Viscometer. The weight of the coconut fiber ash used is 2g, 4g, 6g, 8g, 10g, 15g and 20g. The most optimum weight of coconut fiber ash that can be added is between 6g to 15g as according to American Petroleum Institute (API). It can be concluded that coconut fiber ash really enhanced the Bentonite water-based drilling fluid when a certain amount of weight is added in the drilling fluid.